2018
DOI: 10.1097/spv.0000000000000445
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence in Pregnant Young Women and Adolescents: An Unrecognized At-Risk Group

Abstract: This was a cross-sectional study evaluating the prevalence of UI in pregnant young females and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Risk of bias for the outcome measurement was judged as high for three studies since they did not state the questions used, 21–23 and seven studies were rated of medium risk of bias since the questions were asked in an interview. We judged 24 studies as high risk of bias for study confounding because they did not conduct multivariable analysis and these studies were subsequently judged of medium risk of bias for statistical analysis and reporting 6,21–43 . An additional two studies were judged as medium risk of bias for statistical analysis and reporting because they had not fully reported results 44,45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk of bias for the outcome measurement was judged as high for three studies since they did not state the questions used, 21–23 and seven studies were rated of medium risk of bias since the questions were asked in an interview. We judged 24 studies as high risk of bias for study confounding because they did not conduct multivariable analysis and these studies were subsequently judged of medium risk of bias for statistical analysis and reporting 6,21–43 . An additional two studies were judged as medium risk of bias for statistical analysis and reporting because they had not fully reported results 44,45 …”
Section: Resultsmentioning
confidence: 99%
“…Women with one to three (OR: 1.7 [0.8–3.3]; p = 0.14) or four to eight children (OR: 2.5 [1.0–6.7]; p = .06) were not more likely to experience UI than nulliparous women. Jean‐Michel et al 29 asked 98 women in the second/third trimester concerning UI symptoms in the prior 3 months and found no association (parity ≥1 vs. parity 0: OR: 0.6 [0.1–1.3]; p = 0.18).…”
Section: Resultsmentioning
confidence: 99%
“…Based on these classes the overall bother of UI during pregnancy is mild and in the third trimester mild to moderate. One study reporting on bother of UI in the last 4 weeks of pregnancy reported the highest bother of 57 [42]. This might be due to the rising prevalence over time in pregnancy [29,34,[42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…One study reporting on bother of UI in the last 4 weeks of pregnancy reported the highest bother of 57 [42]. This might be due to the rising prevalence over time in pregnancy [29,34,[42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Urinary incontinence (UI) is the most frequent pelvic floor dysfunction during pregnancy and the postpartum period, with a prevalence in the range of 21%-54% in adolescents and adults, depending on the study design, applied definitions, and sample recruitment. [1][2][3] Despite its temporary condition in most cases, with resolution in the first 3 months after delivery, UI in immediate postpartum may predict the long-term existence of this condition. 2 The UI complaint after this period increases the dysfunction persistence risk for up to 12 years after delivery.…”
Section: Introductionmentioning
confidence: 99%